Characteristics of inorganic phosphorus fractions and their correlations with soil properties in three non-acidic soils - Nai-yu ZHANG; Qiong WANG; Xiao-ying ZHAN; Qi-hua WU; Shao-min HUANG; Ping ZHU; Xue-yun YANG; Shu-xiang ZHANG (Journal of Integrative Agriculture, 2022)
Understanding the characteristics and influences of various factors on phosphorus (P) fractions is of significance for promoting the efficiency of soil P. Based on long-term experiments on black soil, fluvo-aquic soil, and loess soil, which belong to Phaeozems, Cambisols, and Anthrosols in the World Reference Base for Soil Resources (WRB), respectively, five fertilization practices were selected and divided into three groups: no P fertilizer (CK/NK), balanced fertilizer (NPK/NPKS), and manure plus mineral fertilizer (NPKM). Soil inorganic P (Pi) fractions and soil properties were analyzed to investigate the characteristics of the Pi fractions and the relationships between Pi fractions and various soil properties. The results showed that the proportion of Ca10-P in the sum of total Pi fractions was the highest in the three soils, accounting for 33.5% in black soil, 48.8% in fluvo-aquic soil, and 44.8% in loess soil. Long-term fertilization practices resulted in periodic changes in soil Pi accumulation or depletion. For black soil and fluvo-aquic soil, the Pi accumulation was higher in the late period (10–20 years) of fertilization than in the early period (0–10 years) under NPK/NPKS and NPKM, whereas the opposite result was found in loess soil. The Pi accumulation occurred in all Pi fractions in black soil; mainly in Ca8-P, Fe-P, and Ca10-P in fluvo-aquic soil; and in Ca2-P, Ca8-P, and O-P in loess soil. Under CK/NK, the soil Pi was depleted mainly in the early period in each of the three soils. In addition to the labile Pi (Ca2-P) and moderately labile Pi (Ca8-P, Fe-P, Al-P), the Ca10-P in black soil and fluvo-aquic soil and O-P in loess soil could also be used by crops. Redundancy analysis showed that soil properties explained more than 90% of the variation in the Pi fractions in each soil, and the explanatory percentages of soil organic matter (SOM) were 43.6% in black soil, 74.6% in fluvo-aquic, and 38.2% in loess soil. Consequently, decisions regarding the application of P fertilizer should consider the accumulation rate and the variations in Pi fractions driven by soil properties in non-acidic soils.